2020
DOI: 10.1177/0961203320947814
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of belimumab treatment in patients with systemic lupus erythematosus in a clinical practice setting: Results from a 24-month OBSErve study in Argentina

Abstract: Objective To describe clinical effectiveness of belimumab for systemic lupus erythematosus (SLE) in real-world practice in Argentina. Methods This retrospective, observational study analysed medical record data of patients with SLE treated with belimumab in 15 centres in Argentina. Primary endpoint: overall clinical response (assessed on a scale similar to the 6-point Physician Global Assessment) at months 6, 12, 18 and 24, all versus index (belimumab initiation). Secondary endpoints: improvement in disease ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 27 publications
2
16
0
2
Order By: Relevance
“…The present study identified trials published up to 2020, excluding potentially relevant studies published later. One publication from July 2020 reported results from the 24-month Argentina OBSErve study of 81 patients with SLE showing that belimumab treatment leads to clinical improvement and reductions in corticosteroid dose, consistent with the findings presented here [ 42 ]. Similar results were also reported in a recently published post hoc pooled analysis of real-world data from six OBSErve studies [ 43 ], most of which were included in our evaluation.…”
Section: Discussionsupporting
confidence: 87%
“…The present study identified trials published up to 2020, excluding potentially relevant studies published later. One publication from July 2020 reported results from the 24-month Argentina OBSErve study of 81 patients with SLE showing that belimumab treatment leads to clinical improvement and reductions in corticosteroid dose, consistent with the findings presented here [ 42 ]. Similar results were also reported in a recently published post hoc pooled analysis of real-world data from six OBSErve studies [ 43 ], most of which were included in our evaluation.…”
Section: Discussionsupporting
confidence: 87%
“…This was a post hoc pooled analysis (GSK study 206351) of patient-level data pooled from the six retrospective, observational cohort OBSErve studies from 97 study centers based in Argentina (GSK study 201282), Canada (GSK study 117300), Germany (GSK study 117214), Spain (GSK study 200883), Switzerland (GSK study 201232), and the USA (GSK study 117295) [ 11 17 ]. Follow-up times varied between the original studies (OBSErve Canada, Germany, Spain, and Switzerland: 6 months; OBSErve Argentina and USA: up to 24 months), for the current analysis, patient data collected at belimumab start (index date, between September 2012 and March 2016) and at 6 months after index, or at time of discontinuation, were analyzed, because this was the longest duration of follow-up time for which all countries could contribute data (Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Characteristics of included studies. A total of seven RCTs (11)(12)(13)(14)(15)(16)(17) and 19 case series (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36) were included in the analysis, including 6,832 patients with SLE. The details of the aforementioned studies are presented in Tables I and II.…”
Section: Resultsmentioning
confidence: 99%